“I think they consider themselves free from all responsibility”. User Perspectives on Neoliberal Undermining of Welfare Services During the Pandemic - Hrafnhildur Snæfríðar- og Gunnarsdóttir; Ásta Jóhannsdóttir; Freyja Haraldsdóttir (Nordisk Välfärdsforskning)
The pandemic brought to the surface various structural and systemic challenges facing disabled people. Grounded in feminist standpoint theory and critical disability studies, this paper explores the experiences of users of personal assistance (PA) services in Iceland during the pandemic. Altogether eight disabled adults and parents of three disabled children participated in semi-structured interviews. In addition to uncertainties and health concerns associated with COVID-19, the pandemic introduced novel complications and administrative responsibilities for users of personal assistance. Unacknowledged by municipalities, these burdens proved onerous and stressful to participants, and led in some cases to dangerous situations that could have been avoided. The findings highlight the process through which this was facilitated: by the increased responsibilization of service users and the influence of market ideology and austerity. Framing the services as a private-sector-inspired contract enabled municipalities to evade their responsibilities towards disabled service users, in stark contrast to the social justice and human rights understanding in which the services are embedded. The paper is a contribution to research problematizing neoliberal undermining of welfare services and the commodification of fundamental values such as welfare and the human rights of disabled people.